SS-OCTA assessment of fundus microvascular changes and their correlation with coronary lesion severity in severe coronary heart disease - Dandan Zong; Huiyu Xi; Yewen Ni; Tian Liang; Meishuang Li; Jun Zhou; Haiyang Liu (Scientific Reports)
Abstract This study aimed to quantify fundus microvascular alterations in patients requiring revascularization for coronary heart disease (CHD) using swept-source optical coherence tomography angiography (SS-OCTA) and to investigate the correlation between these alterations and the severity of coronary artery lesions. SS-OCTA was employed to assess the fundus neurovascular parameters of all participants, while the Gensini score was utilized to gauge the severity of coronary artery lesions in observation group. A total of 98 participants (49 CHD patients and 49 controls) were included. Analysis of the SS-OCTA parameters revealed that the vascular density (VD) of the superficial vascular plexus (SVP), the superficial vascular complex (SVC), the intermediate capillary plexus (ICP) in the parafoveal region, the mean ICP in the macula, deep capillary plexus (DCP) and deep vascular complex (DVC) in each macular region were significantly reduced in the observation group compared to the control group (P < 0.05). Multivariate logistic regression indicated that lower VD values in the SVP, SVC, ICP, DCP and DVC across macular regions were significantly associated with an increased likelihood of severe CHD (OR < 1, P < 0.05). ROC curve analysis revealed that the maximum area under the curve for overall DCP VD in the macula was 0.707, with a cutoff value of 19.64, sensitivity of 65.30%, and specificity of 73.50%. In CHD group, Pearson correlation analysis demonstrated a negative correlation between the Gensini score and mean DCP VD (r = − 0.491, P < 0.001). Retinal VD in patients requiring revascularization for CHD is significantly lower compared to healthy controls. SS-OCTA-based retinal microvascular damage assessment is a valuable tool for risk stratification and early intervention in CHD.